2008
DOI: 10.1016/j.cmet.2008.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Risk Begins In Utero

Abstract: Both intrauterine and postnatal environments contribute to diabetes risk. A recent paper highlights epigenetic mechanisms underlying beta cell dysfunction associated with intrauterine growth retardation, including repressive histone modification and DNA methylation during postnatal life. Thus, intrauterine stress can initiate a disturbing epigenetic cascade of progressive transcriptional repression linked to beta cell failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…First, alterations in nutrition during development can alter epigenetic marks, thus regulating gene expression through DNA methylation (12,(17)(18)(19) and/or histone modifications (17,20,21). Interestingly, such epigenetic modifications may progress with aging during postnatal life, in association with metabolic phenotypes, as recently observed at the pancreatic duodenal homeobox-1 and GLUT4 locus in rodent models of intrauterine programming (33)(34)(35). If these epigenetic changes occur in the germ line, they can be inherited through meiosis (22)(23)(24), thus providing a plausible explanation for intergenerational effects, transmitted via either maternal or paternal lines.…”
Section: Discussionmentioning
confidence: 99%
“…First, alterations in nutrition during development can alter epigenetic marks, thus regulating gene expression through DNA methylation (12,(17)(18)(19) and/or histone modifications (17,20,21). Interestingly, such epigenetic modifications may progress with aging during postnatal life, in association with metabolic phenotypes, as recently observed at the pancreatic duodenal homeobox-1 and GLUT4 locus in rodent models of intrauterine programming (33)(34)(35). If these epigenetic changes occur in the germ line, they can be inherited through meiosis (22)(23)(24), thus providing a plausible explanation for intergenerational effects, transmitted via either maternal or paternal lines.…”
Section: Discussionmentioning
confidence: 99%
“…In rodent models that mimic low birth weight in humans by food restriction or restriction of placental flow of pregnant dams, it has now been clearly demonstrated that not only do the low birth weight offspring have an increased risk of diabetes, but this risk is passed on to the second generation, probably through effects on intrauterine and early postnatal nutritional effects on genetic imprinting and/or epigenetic regulation of gene expression or development (Sharif et al, 2007; Ozanne and Constancia, 2007; Jimenez-Chillaron et al, 2006). Moreover, these epigenetic marks, while resulting from early life exposures, can actually progress during postnatal life and thus contribute to age-dependent transcriptional repression of key metabolic genes, as has recently been demonstrated for the β cell transcription factor PDX1 (Park et al, 2008) and the insulin-sensitive glucose transporter GLUT4 (Raychaudhuri et al, 2008, Woo and Patti, 2008). …”
Section: The Emerging Genetic Architecture Of Type 2 Diabetesmentioning
confidence: 94%
“…Person-years at risk were calculated for each employee beginning January 1, 1985, and ending at the closing date of the study (December 31,2005) or the date of death, whichever came first. Hazard ratios (HRs) for cumulative number of risk factors were calculated using a Cox proportional hazards model (SAS PHRGEG procedures) adjusted for age and gender.…”
Section: Methodsmentioning
confidence: 99%